(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This review focused on studies concentrated on identifying phytochemicals in Araucaria columnaris. This species is popular as an ornamental plant and its pharmacological activities and therapeutic uses are not commonly known. We screened various bibliographic databases and retrieved 13 relevant studies, which explored Araucaria columnaris chemical constitution.